Faktor-Faktor yang Mempengaruhi Kejadian Asam Urat pada Lansia di Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2025 - Rica Meiriska Sari; Fiya Diniarti; Hengki Tranado (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Uric acid, commonly known as gouty arthritis, is the end product of purine metabolism, which is a component of nucleic acids found in the cell nucleus. Data from the Indonesian Ministry of Health for 2022 shows an increase in gout cases from 72,675 in 2021 to 102,995 in 2022. At the Jembatan Kecil Community Health Center in Bengkulu City, the number of elderly people suffering from uric acid was recorded at 80 in 2025. The incidence of gout is influenced by various factors such as physical activity, purine intake, and genetic history. This study aims to identify the factors influencing the incidence of gout among the elderly at the Jembatan Kecil Community Health Center in Bengkulu City in 2025. The method used in this study was an analytical study with a cross-sectional design. The study population consisted of all elderly individuals visiting the Jembatan Kecil Community Health Center in Bengkulu City, with a sample size of 107 respondents. The sampling technique used was accidental sampling. The results of the univariate analysis showed that the majority of respondents (64.5%) had low physical activity levels; a portion of respondents had low and moderate purine intake (35.5% each); the majority of respondents (51.4%) had a family history of gout; and the majority of respondents (51.4%) had elevated uric acid levels. The results of the bivariate Chi-square test analysis indicate that there is a significant association between physical activity and the incidence of gout (p = 0.000), a significant association between purine intake and the incidence of gout (p = 0.000), and a significant association between family history and the incidence of gout in the elderly (p = 0.000). It is hoped that the elderly can maintain a healthy diet and increase their physical activity to prevent an increase in uric acid levels